Debtors Management and Financial Performance on Microfinance Finance Institutions: A Case Study at Pride Microfinance, Bukoto - Lydia Akiror (Uganda Christian University, 2023)
The management of a firm’s liquidity is necessary for all businesses, small, medium or large. When a business does not manage its liquidity well, it will have cash shortages and as a result, they experience problem paying its obligations when they fall due. Debtors’ management is important because of its effect on the firm’s profitability and risk, and consequently its value. To boost the growth of micro finance institutions sector, debtors’ management must be put at the fore front since it forms the basis of almost each and every activity and thus it should be fully implemented in all levels of the organization, this will help shift the focus from following on doubtful debts to new ways of doing business, the main objective of debtors’ management is to increase shareholder’s wealth and as well as the firm’s profits. However, according to (Munyiri,2006) debtors’ management challenges continue to hinder the achievement of objectives and has led to poor performance, too much funding and failure to do background check up before appraisal is done, this has led to some branches closing due to lack of business and too much debt as the commercial banks are striving in the money market their counterparts in micro finance sector are struggling to recover the outstanding amounts leading to poor performance. According to (Gathurithu,2011) micro finance institution offer similar services like banks but their performance is not something to be proud of. It is against this background that I conducted a study on debtor’s management and financial performance of micro finance institutions. The general objective of the study was to find out how debtors management affects the financial performance of pride micro finance while the specific objectives were: to find out whether credit extension policies affects the financial performance, to examine how debt monitoring and control affects the financial performance and to assess the effect of debt collection policy on financial performance of pride micro finance
This is a dissertation.